2022
DOI: 10.1016/j.isci.2021.103574
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid primed mTOR activity is essential for heart regeneration

Abstract: Summary Heart disease is the leading cause of death with no method to repair damaged myocardium due to the limited proliferative capacity of adult cardiomyocytes. Curiously, mouse neonates and zebrafish can regenerate their hearts via cardiomyocyte de-differentiation and proliferation. However, a molecular mechanism of why these cardiomyocytes can re-enter cell cycle is poorly understood. Here, we identify a unique metabolic state that primes adult zebrafish and neonatal mouse ventricular cardiomyoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 78 publications
1
22
0
Order By: Relevance
“…During activation of mTOR signaling, mammalian TOR complex 1 (mTORC1) activates ribosomal protein S6 kinase (S6K) (Magnuson et al, 2012), which subsequently induces phosphorylation of ribosomal protein S6 (rpS6), a component of the S40 ribosome (Ruvinsky and Meyuhas, 2006). Furthermore, rpS6 phosphorylation by S6K is required for regeneration of zebrafish fin (Hirose et al, 2014), heart (Miklas et al, 2022), and retinal pigment epithelium (Lu et al, 2022). Thus, we conducted labeling of zebrafish telencephalon at 3 dpl with anti-phospho-rpS6 antibody.…”
Section: Resultsmentioning
confidence: 99%
“…During activation of mTOR signaling, mammalian TOR complex 1 (mTORC1) activates ribosomal protein S6 kinase (S6K) (Magnuson et al, 2012), which subsequently induces phosphorylation of ribosomal protein S6 (rpS6), a component of the S40 ribosome (Ruvinsky and Meyuhas, 2006). Furthermore, rpS6 phosphorylation by S6K is required for regeneration of zebrafish fin (Hirose et al, 2014), heart (Miklas et al, 2022), and retinal pigment epithelium (Lu et al, 2022). Thus, we conducted labeling of zebrafish telencephalon at 3 dpl with anti-phospho-rpS6 antibody.…”
Section: Resultsmentioning
confidence: 99%
“…Since leucine concentration rises in the postnatal week, does the concentration of BCAA also affect the ability of cardiomyocytes to proliferate? Researchers found that cardiomyocyte injury initiated Wnt/βcatenin signaling during zebrafish cardiomyocyte regeneration, which in turn initiated mTOR activation and metabolic remodeling (97). As previously described, Wnt/β-catenin signaling pathway promoted glycolysis and activated mTOR signaling pathway together with BCAAs (91,98).…”
Section: Amino Acid Metabolism Followed By Heart Regenerationmentioning
confidence: 75%
“…According to a recent study by Miklas et al, amino acid-induced activation of mTOR signaling is required for zebrafish heart regeneration. Moreover, CM cell cycle reentry and proliferation (suppressed as part of CM maturation) in the first week of neonatal mouse heart development and in vitro hESC-CMs were also shown to be dependent on activation of Wnt/B-catenin and mTORC1 signaling ( 56 ). In fact, Wnt/B-catenin activates the mTOR pathway through inhibition of GSK3, an activator of the mTOR upstream inhibitor TSC2.…”
Section: Signaling Pathways Potentially Associated With Human Induced...mentioning
confidence: 99%